2017
DOI: 10.1515/qmetro-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Super-thermal light for imaging applications

Abstract: Abstract:We report on a new classical light source useful for ghost-imaging applications. The light is obtained by frequency doubling a conventional speckle pattern having an overall multi-mode thermal distribution. The frequency-doubled light acquires a super-thermal distribution, which induces higher correlations at a beam splitter and, as a consequence, a higher visibility in ghostimaging protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Also, optical beams with gfalse(2false)>2$g^{(2)}>2$ are called super‐thermal light fields. [ 34,35 ] As demonstrated in Figure 1e–g, these random phase screens thermalize the initial coherent laser beam to produce a degree of second‐order coherence gfalse(2false)>1$g^{(2)}>1$. In our experiment, we are able to preserve the coherent statistics of the initial beam by encoding phase screens with Fried's parameters r 0 that tend to infinity.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Also, optical beams with gfalse(2false)>2$g^{(2)}>2$ are called super‐thermal light fields. [ 34,35 ] As demonstrated in Figure 1e–g, these random phase screens thermalize the initial coherent laser beam to produce a degree of second‐order coherence gfalse(2false)>1$g^{(2)}>1$. In our experiment, we are able to preserve the coherent statistics of the initial beam by encoding phase screens with Fried's parameters r 0 that tend to infinity.…”
Section: Resultsmentioning
confidence: 79%
“…Also, optical beams with g (2) > 2 are called super-thermal light fields. [34,35] As demonstrated in Figure 1e-g, these random phase screens The experiment is performed using a green laser centered at 532 nm. The initial beam is spatially cleaned and expanded using a 4-f system to match the size of the digital micro-mirror device (DMD).…”
Section: Resultsmentioning
confidence: 99%
“…where L is the crystal length. Given the link between the incoming light intensity and the second-harmonic one in Equation 10, it is possible to find a relation between the two corresponding light distributions [11,14,15]. Upon writing Equation 10as…”
Section: Classical Regimementioning
confidence: 99%
“…In particular, it has been shown that light states, more correlated than the thermal ones, may lead to higher visibility, higher contrast or higher SNR 31 , 32 . Among them, it is worth mentioning that the statistics of frequency-doubled thermal states is definitely “super-thermal”, having it intensity fluctuations larger than those of a thermal field 33 , 34 . Super-thermal statistics can be also obtained by using a sequence of diffusers 35 – 39 , as some of us have experimentally demonstrated for two rotating ground-glass disks 40 by measuring the photon-number statistics in the mesoscopic intensity regime by means of photon-number-resolving detectors 41 .…”
Section: Introductionmentioning
confidence: 99%